The story of forgetting a novel - Block, Stefan Merrill 1982- (Faber & Faber, 2009)
"Fifteen-year old Seth Waller is devastated when his mother is diagnosed with a rare, early-onset form of Alzheimer's. When he was growing up, his mother always brushed aside questions about her past and family, and Seth realises that soon he will lose his chance to find out any more. He decides to uncover the truth about her life, their family history and the condition, and what he discovers is more surprising than he ever could have imagined. Inspired partly by the author's own family history, The story of forgetting is a moving and exhilarating novel of love, loss, hope and genetic destiny."
Keywords: Fiktionale Darstellung